2015
DOI: 10.1128/iai.00624-15
|View full text |Cite
|
Sign up to set email alerts
|

Role of Host Cell-Derived Amino Acids in Nutrition of Intracellular Salmonella enterica

Abstract: The facultative intracellular pathogen Salmonella enterica resides in a specific membrane-bound compartment termed the Salmonella-containing vacuole (SCV). Despite being segregated from access to metabolites in the host cell cytosol, Salmonella is able to efficiently proliferate within the SCV. We set out to unravel the nutritional supply of Salmonella in the SCV with focus on amino acids. We studied the availability of amino acids by the generation of auxotrophic strains for alanine, asparagine, aspartate, gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
53
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 46 publications
6
53
0
Order By: Relevance
“…Exploitation of host amino acid metabolism by intracellular bacteria is an emerging paradigm (55,56). There is prominent overlap between the amino acid auxotrophies of C. burnetii, L. pneumophila, and other intracellular bacteria and the essential amino acids of the mammalian host cell (57,58).…”
Section: Discussionmentioning
confidence: 99%
“…Exploitation of host amino acid metabolism by intracellular bacteria is an emerging paradigm (55,56). There is prominent overlap between the amino acid auxotrophies of C. burnetii, L. pneumophila, and other intracellular bacteria and the essential amino acids of the mammalian host cell (57,58).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that asparagine biosynthesis is also important for S. Typhimurium virulence. S. Typhimurium bacteria lacking both asparagine biosynthesis genes asnA (STM3877) and asnB (STM0680) are attenuated for survival and replication inside host cells (22), and are unable to compete with wild-type S. Typhimurium for colonization of murine spleen (23). Furthermore, it has been reported that S. Typhimurium exploits fructoseasparagine for growth in the inflamed intestine (24).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with their parasitic nature, many Apicomplexan parasites have lost some amino acid biosynthetic capabilities; however, the Toxoplasma genome encodes a relatively full repertoire of biosynthetic machinery, perhaps reflecting the wide variety of intracellular environments in which it resides [2, 3]. Computational models of Toxoplasma metabolism have successfully predicted many of its metabolic capabilities, such as acetyl-CoA biosynthesis, but have made conflicting predictions on whether tachyzoites are auxotrophic for tyrosine [2, 4, 5].…”
Section: Introductionmentioning
confidence: 99%